The Effect of Quality of Work Life on Employee Engagement At PT. X in Sidoarjo - Rara Angtika; Setya Haksama (Universitas Pahlawan Tuanku Tambusai, 2025)
Work engagement has become the company's greatest concern and priority in the last two decades. One factor influencing work engagement is the quality of work life. The total of 183 employees left PT. X in 2021-2023. This study aims to analyzed the relationship between quality of work life and work engagement in PT. X Sidoarjo. This research was a quantitative study with a cross-sectional design. This research was conducted in PT. X Sidoarjo in April 2024. 148 employees participated. The sampling technique used was simple random sampling, and 60 respondents were obtained. The instruments used were the Work-Related Quality of Life (WRQoL) Scale and the Utrecht Work Engagement 9-Scale. There was no dimension whose average reaches a high quality of work life. Dimensions with a low average quality level were job career satisfaction, working conditions, and stress at work. The majority of employees had a medium level of work-life quality. Meanwhile, work engagement was at a low and high level. Quality of work life has been proven to influence employee engagement. Companies are expected to be able to provide education and training to develop skills related to the work the employee is carrying out. Companies are also expected to be able to evaluate stress sources in employees.